The Influence of Powerful Interactive Joyful Teachers, Learning Motivation, And Learning Behavior on Academic Achievement - Ning Tresno Mulyani; Suriswo Suriswo; Rahmad Agung Nugroho (Magistra)
This study aims to determine the effect of powerful interactive joyful teachers, learning motivation, and learning behavior on academic achievement. The research sample was 130 students from 192 grade V elementary school students in Dabin 3 Regional Coordinator, Ampelgading District, Pemalang Regency, with a proportional random sampling technique. The source of research data used was primary data obtained directly from respondents with a questionnaire. The data processing tool used was SPSS for Windows version 21. Data analysis used multiple linear regression analysis. From the data test and analysis conducted, this study provides empirical evidence as follows: powerful interactive joyful teachers, learning motivation, and learning behavior have a positive and significant effect on academic achievement.